Abrams’ Law Formulation for Blended Cement Paste Incorporated with Ground Ferronickel Slag - Djayaprabha, Herry Suryadi; Fatharani, Ashila Hasya (UKaRsT, 2024)
Ground ferronickel slag (GFS) is a form of an industrial waste by-product generated during the smelting process of nickel ore that has been crushed and ground into fine powder. GFS is a pozzolanic substance that may be employed as an environmentally beneficial binding agent when blended with Portland cement. This research aims to apply the Abrams Law formulation to blended cement combined with GFS. GFS was utilized as a Portland cement composite (PCC) replacement at varying percentages of 0, 10, 20, 30, 40, and 50 wt.%. The blended cement paste incorporated with GFS was tested at three water to cementitious material ratio (w/cm) levels of 0.4, 0.5, and 0.6. After samples have been made, a compressive strength test is carried out. The research results showed that at 28 days, the optimum amount of GFS was found in the percentage of 20 wt.% induced the compressive strength by 40.41 MPa with a w/cm of 0.4. The equations based on Abrams’ Law have been proposed for estimating the correlation of 28-day compressive strength with w/cm in the range from 0.4 to 0.6. In addition, the hardened densities of binary blended cement paste were investigated. It was found that the density decreased with an increase of w/cm. The proposed equations provide the beneficial interpretation for estimating the compressive strength of blended cement paste based on the w/cm..